2016
DOI: 10.1097/wco.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Interictal high-frequency oscillations in focal human epilepsy

Abstract: Purpose of review Localization of focal epileptic brain is critical for successful epilepsy surgery and focal brain stimulation. Despite significant progress, roughly half of all patients undergoing focal surgical resection, and most patients receiving focal electrical stimulation, are not seizure free. There is intense interest in high-frequency oscillations (HFOs) recorded with intracranial electroencephalography as potential biomarkers to improve epileptogenic brain localization, resective surgery, and foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 69 publications
2
51
0
1
Order By: Relevance
“…There is strong evidence that HFOs are a biomarker of epileptogenic brain (Jacobs et al, 2008), and utilizing HFO rates for clinical applications will require accurate HFO detection (Cimbalnik et al, 2016), and an agreed upon ripple classification scheme. Quantifying HFO rates using iEEG recordings from the epilepsy monitoring unit or operating room has been proposed as a means to identify epileptogenic brain regions (van ’t Klooster et al, 2015a, 2015b) and studies have suggested that simultaneous HFOs and inter-ictal epileptiform spikes (IES) are stronger indicators of epileptogenic tissue than IES events alone (Jacobs et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that HFOs are a biomarker of epileptogenic brain (Jacobs et al, 2008), and utilizing HFO rates for clinical applications will require accurate HFO detection (Cimbalnik et al, 2016), and an agreed upon ripple classification scheme. Quantifying HFO rates using iEEG recordings from the epilepsy monitoring unit or operating room has been proposed as a means to identify epileptogenic brain regions (van ’t Klooster et al, 2015a, 2015b) and studies have suggested that simultaneous HFOs and inter-ictal epileptiform spikes (IES) are stronger indicators of epileptogenic tissue than IES events alone (Jacobs et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of interictal HFOs is usually considered to be the most important parameter [26]. The rates of HFOs vary across different studies.…”
Section: High-frequency Oscillationsmentioning
confidence: 99%
“…While early studies were focused on the frequency band of the HFOs oscillations to classify them as pathologic or physiologic, considering the wide range of overlapping pHFOs and nHFOs frequencies [3,4,11,18,4244], more recent studies have explored other frequency-independent characteristics of HFOs: rate, amplitude, and duration [4552]. Regions showing a high rate of interictal HFOs have been correlated with pathological epileptic tissue in different studies [2,15,48,5254].…”
Section: Hfos Rate Amplitude and Durationmentioning
confidence: 99%
“…While there has been significant progress in automated detection of HFOs, reliably distinguishing normal physiological oscillations from pathological epileptiform oscillations [2,11,15] remains a fundamental challenge in epileptology [1618]. …”
Section: Introductionmentioning
confidence: 99%